Sustainable manufacturing tactics and cross-functional factory modelling - Despeisse, Melanie; Oates, Michael R.; Ball, Peter D. (Elsevier, 2013)
Manufacturers are under increasing pressure from stakeholders and stricter regulations to reduce the environmental impact of their activities. The research on sustainability in general and on sustainable manufacturing in particular is rapidly developing and crossing disciplinary boundaries. There are numerous well-developed concepts for industrial sustainability which can contribute to sustainable manufacturing, but there is a gap in knowledge on how to achieve the desired conceptual aims at operational level. There also is a growing volume of industrial cases on sustainable manufacturing practices, but little is known on how these improvements were conceived. Additionally, the means by which improvement options can be reproduced and modelled is lacking. This paper presents a tactics library to provide a connection between those generic sustainability concepts and more specific examples of operational practices for resource efficiency in factories. Then a factory modelling approach is introduced to support the use of tactics by combining the analysis of building energy and manufacturing process resource flows. Finally a step-by-step guide in the form of a workflow for factory modelling and resource flow analysis is presented and tested via a prototype tool. The aim was to provide guidelines for manufacturers to undertake the sustainability journey by guiding them through the steps of factory modelling, resource flow analysis and improvement opportunities identification. The paper has implications for researchers and practitioners as it demonstrates how factories can sustainably be improved in a structured, systematic and cross-functional way. This contributes to the need for expanding the scope of analysis beyond functional boundaries to apply sustainability at factory level.
Keywords: Sustainable manufacturing tactics; Industrial sustainability; Factory modelling; Resource flows